1998
DOI: 10.1038/1270
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of epithelial stem-cell compartments in the small intestine of mice lacking Tcf-4

Abstract: Mutations of the genes encoding APC or beta-catenin in colon carcinoma induce the constitutive formation of nuclear beta-catenin/Tcf-4 complexes, resulting in activated transcription of Tcf target genes. To study the physiological role of Tcf-4 (which is encoded by the Tcf7/2 gene), we disrupted Tcf7/2 by homologous recombination. Tcf7/2-/- mice die shortly after birth. A single histopathological abnormality was observed. An apparently normal transition of intestinal endoderm into epithelium occurred at approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
1,117
3
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,444 publications
(1,157 citation statements)
references
References 31 publications
30
1,117
3
7
Order By: Relevance
“…Wnt signaling plays an important role in the maintenance of the intestinal crypt containing the stem cells and undifferentiated progenitor cells 14,15 . In the gastric gland, Wnt signaling also keeps the progenitor cells undifferentiated in the isthmus of the gastric gland, as we have shown that the number of progenitors increased significantly in the K19-Wnt1 mouse stomach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt signaling plays an important role in the maintenance of the intestinal crypt containing the stem cells and undifferentiated progenitor cells 14,15 . In the gastric gland, Wnt signaling also keeps the progenitor cells undifferentiated in the isthmus of the gastric gland, as we have shown that the number of progenitors increased significantly in the K19-Wnt1 mouse stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Given that Wnt signaling is essential for maintaining the intestinal crypt that contains epithelial progenitor cells and stem cells 14,15 , we examined gastric epithelial differentiation in the K19-Wnt1 mice. The trefoil factor 2 (TFF2) was used as an undifferentiated epithelial marker, because it was detected in the small isthmal cells ( Figure 3A and B) where β-catenin accumulated in both the nucleus and cytoplasm ( Figure 3C).…”
Section: Suppression Of Gastric Epithelial Differentiation By Wnt Actmentioning
confidence: 99%
“…Symmetrical stem cell divisions provide a mechanism to increase the stem cell population after stem cell loss, but symmetrical divisions can also lead to a dangerous escalation of stem cell numbers, as seen with disruption of asymmetrical neuroblast cell division in Drosophila melanogaster that leads to lethal, expansive, tumourlike lesions when such cells are transplanted into adult hosts [15]. Alternatively, lack of appropriate signalling can lead to stem cell exhaustion, as seen in mice lacking Tcf-4 and so unable to form β-catenin-Tcf-4 complexes essential for Wnt signalling in the small intestine ( Figure 4) [16].…”
Section: Self-renewal and The Stem Cell Nichementioning
confidence: 99%
“…This canonical Wnt signaling (Wnt/β-catenin signaling) plays a key role in the maintenance of intestinal stem cells and progenitor cells 2,3 . Moreover, the constitutive activation of Wnt/β-catenin signaling causes gastrointestinal tumorigenesis in both human 4,5 and mice 6,7 .…”
Section: Introductionmentioning
confidence: 99%